The effect of the air flow on the temperature of the PV panel examined for two BIPV panels of different shape - Agathokleous, Rafaela; Aresti, Lazaros; Florides, Georgios A.; Kalogirou, Soteris A.; Christodoulides, Paul (My University, 2014)
During the last few years photovoltaic (PV) materials are increasingly incorporated (or integrated) into the construction of buildings for generating electrical power. This integration is done either on the facade or roof of the building. This integration creates also heat which if not removed can create cooling requirements in buildings, especially in summertime, whereas during winter this heat can be used effectively to cover part of the building heating load. Additionally, if this heat is not removed it will also lower the efficiency of the PV panels. Consequently there is a challenge to find solutions to remove this heat resulting from the building integrated PV (BIPV) panels. The aim of this study is to examine the effect of air flow in the air gap between the integrated PV panel and the building’s wall on the temperature of the PV panel. The examination of the effect of the air gap of a BIPV system is very important as it can lead to better understanding of the conditions that allow the higher efficiency of the PV panel and accordingly the increase of the efficiency of the BIPV system. Two different PV modules are examined; the one has a flat surface as the conventional PV panels and the other one has a repeated pi-section surface with different air gap widths through its length and thus different air velocity in the two types of sections. To formulate the heat exchange process for a fluid flowing between the PV panel and the building wall, time-dependent, partial heat transfer differential equations (PDEs) are used and solved with the COMSOL Multiphysics simulations program. Initially, the air-gap width is varied keeping a steady velocity, and subsequently the air velocity is varied keeping constant the air gap and the effect were studied in respect to the temperature of the PV-panel. The runs were carried out for three orientations for the panel facing east, south and west. For the PV module with the flat surface the simulations showed that for an air gap width of 0.02 m, an air velocity of 0.5 m/s can lower the mean temperature of the panel from 77°C to 39°C. For the PV module with non-flat surface (repeated pi-section) that has various air gap widths, the air velocity in the air-gap between the PV-panel and the building wall lowers the mean temperature of the panel by about 35°C allowing for a significant increase in its efficiency.
Keywords: Photovoltaic panels; Photovoltaic; Building integrated panels